Answer:
Therefore, ( 1 , 1 ) is the Solution to the Given Equations
[tex]y=2x-1[/tex]
[tex]5x-4y=1[/tex]
Step-by-step explanation:
Given:
[tex]y=2x-1[/tex] ..............Equation ( 1 )
[tex]5x-4y=1[/tex] ..............Equation ( 2 )
To Find:
x = ?
y = ?
Solution:
[tex]y=2x-1[/tex] ..............Equation ( 1 )
[tex]5x-4y=1[/tex] ..............Equation ( 2 )
Substituting equation 1 in equation 2 we get
[tex]5x-4(2x-1)=1\\applying\ distributive\ property\ we\ get\\5x-8x+4=1\\\\-3x=1-4=-3\\\\x=\frac{-3}{-3}=1\\ \therefore x = 1\\[/tex]
Substituting 'x' in Equation ( 1 ) we get
[tex]y=2\times 1-1\\\\y=1\\\\\therefore y =1\\[/tex]
Therefore, ( 1 , 1 ) is the Solution to the Given Equations
[tex]y=2x-1[/tex]
[tex]5x-4y=1[/tex]